A poética do tempo nas instantâneas de Andrei Tarkóvski - Miriam Chiara Oliveira dos Santos (2015)
The following dissertation investigates the forms of time as they appear in Andrei Tarkovsky's photographs, and especially in his Polaroid snapshots made between 1979 and 1984. In them, one experiences time from a still image or, according to Plato, as mobile images of eternity. It is considered here that the temporal phenomenon is present in their power of resonance because it reawakens the observer's memories as a faint reminder. They are images agents, as defined by Cicero, they evoke not only beings and places but the atmosphere that surrounds them. The condensed time on the image and its apparent motion will be discussed in dialogue with the work of other artists. Time's constituent elements - memory, eternity, instant - will be explored in the light of philosophers such as Plato, Plotinus, Sant Augustine and the artist himself. Art's spiritual aspect touch all of Tarkovsky's thought about time. Finally, we-ll aproach the notion of Ekphrasis its relationship with the image of absence and the way in which the artist linked the lack of plenitude of man with the emptying of his experience of time.